Penguatan Literasi Keuangan Melalui Pelatihan Pengelolaan Keuangan Bagi Pelajar IPNU–IPPNU Kota Semarang - Herawati, Mesi; Novita, Yeyen; Alfianto, Achmad Nur; Khusni, Kholilatul; Taujiharrahman, Darma (Yayasan Sagita Akademia Maju, 2025)
This community service program aimed to improve the financial literacy of IPNU-IPPNU student members in Semarang City through financial management training. The activity focused on two main aspects: personal financial management, including budgeting, saving, basic investment, and debt control; and organizational financial management, including budgeting, recording financial transactions, and accountability reporting. The implementation consisted of three main stages: an initial survey to measure participants’ financial literacy, a two-day interactive workshop with practical exercises and case discussions, and an evaluation through post-tests and group interviews. The results showed a significant improvement in participants’ understanding and skills in managing both personal and organizational finances. Moreover, participants demonstrated greater awareness of the importance of financial governance. This program demonstrates that brief yet structured financial literacy training can have a significant impact on knowledge and awareness, although sustained mentoring is necessary to ensure long-term behavioral change.